Karakteristik morfologi dan sitologi tanaman Sutra Bombay (Portulaca grandiflora Hook) hasil poliploidisasi dengan kolkisin pada berbagai konsentrasi dan frekuensi aplikasi - Betty Perdana Sari; Karno Karno; Syaiful Anwar (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2017)
Moss Rose (Portulaca grandiflora Hook) is one of the ornamental plants and medicinal plants. The purpose of this research was to evaluate cytological and morphological responses of Moss Rose (Portulaca grandiflora) with colcichine treatment. Colcichine treatment was done with drop method technique in different concentrations and different frequency of application. This research used Completely Randomized Design in 4x3 factorial arrangement and used descriptive analysis to compare diploid plant and tetraploid plant characters. The first factor was variation of cholcichine concentration which were K0 (0%), K1 (0.1%), K2 (0.3%), and K3 (0.6%). The second factor was variation of application frequency which were A1 (2 drop per day for a day), A2 (2 drop per day for 2 days), and A3 (2 drop per day for 3 days). The observed parameters were shoot response by colcichine treatment, number of chromosomes, length and width of stomata, stomata density, stem diameter, flower diameter, plant high, fresh weight, number of branches, and number of leaves. The result showed that Moss Rose’s shoot was intolerant with colcichine treatment in high concentration and long time application. The tetraploid plants was randomly produced by a number of treatment which were 0.1% colcichine 2 drops for 3 days, 0.3% colcichine 2 drops for 2 days, 0.6% colcichine 2 drops for 2 days, and 0.6% colcichine 2 drops for 3 days. The shoot’s growth was inhibited. The induced of tetraploid plant in Moss Rose was accompanied by double chromosome number as 2n=4x=36, larger stomata (length and width), lower stomata density, and higher morphological characters. Moss Rose (Portulaca grandiflora Hook) is one of the ornamental plants and medicinal plants. The purpose of this research was to evaluate cytological and morphological responses of Moss Rose (Portulaca grandiflora) with colcichine treatment. Colcichine treatment was done with drop method technique in different concentrations and different frequency of application. This research used Completely Randomized Design in 4x3 factorial arrangement and used descriptive analysis to compare diploid plant and tetraploid plant characters. The first factor was variation of cholcichine concentration which were K0 (0%), K1 (0.1%), K2 (0.3%), and K3 (0.6%). The second factor was variation of application frequency which were A1 (2 drop per day for a day), A2 (2 drop per day for 2 days), and A3 (2 drop per day for 3 days). The observed parameters were shoot response by colcichine treatment, number of chromosomes, length and width of stomata, stomata density, stem diameter, flower diameter, plant high, fresh weight, number of branches, and number of leaves. The result showed that Moss Rose’s shoot was intolerant with colcichine treatment in high concentration and long time application. The tetraploid plants was randomly produced by a number of treatment which were 0.1% colcichine 2 drops for 3 days, 0.3% colcichine 2 drops for 2 days, 0.6% colcichine 2 drops for 2 days, and 0.6% colcichine 2 drops for 3 days. The shoot’s growth was inhibited. The induced of tetraploid plant in Moss Rose was accompanied by double chromosome number as 2n=4x=36, larger stomata (length and width), lower stomata density, and higher morphological characters.